2009
DOI: 10.1038/jid.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Low Zone Tolerance Requires ICAM-1 Expression to Limit Contact Hypersensitivity Elicitation

Abstract: Painting subsensitizing doses of contact sensitizers on skin (low-dose tolerization) induces antigen (Ag)-specific tolerance, known as low zone tolerance (LZT), which has been experimentally demonstrated by the inhibition of contact hypersensitivity (CHS). Although LZT resulted from the inhibition of the sensitization phase, the effects on the effector/elicitation phase remain unknown. L-selectin and ICAM-1 regulate leukocyte influx into inflamed tissues during the elicitation phase of CHS. LZT was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Likewise, the use of anti-ICAM-1 or anti-LFA-1 (ICAM-1 ligand) antibodies inhibits the rolling process and migration of T lymphocytes to local lymph nodes during an ongoing inflammatory response (Teijeira et al 2017 ). Moreover, tolerance to low doses of allergens applied to the skin of mice was associated with the abolition of elevated ICAM-1 expression in the effector phase of the CHS reaction (Komura et al 2009 ). We observed that all antidepressants lowered ICAM-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the use of anti-ICAM-1 or anti-LFA-1 (ICAM-1 ligand) antibodies inhibits the rolling process and migration of T lymphocytes to local lymph nodes during an ongoing inflammatory response (Teijeira et al 2017 ). Moreover, tolerance to low doses of allergens applied to the skin of mice was associated with the abolition of elevated ICAM-1 expression in the effector phase of the CHS reaction (Komura et al 2009 ). We observed that all antidepressants lowered ICAM-1 gene expression.…”
Section: Discussionmentioning
confidence: 99%